SEARCH FOR NEW MARKETS OF UKRAINIAN HONEY UNDER THE CONDITIONS OF THE COVID-19 PANDEMIC - STAROSTINA, ALLA; BILOVODSKA, OLENA; PANASIUK, YULIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Ukraine produces more honey than the domestic market consume, which means that Ukraine has sufficient potential for honey exports. The main problems of the honey market of Ukraine are the shadowing of the market, low export price of honey and low consumer awareness of honey of Ukrainian origin. Due to the spread of the Covid-19 pandemic on the world market, the demand for honey rises. This is an opportunity for Ukraine to increase honey exports and enter new markets. It will help maintain a leading position in the world market in honey exports, increase the competitiveness of local honey producers and consumer awareness of Ukrainian honey and the build of the country’s brand as a reliable and responsible producer. The Middle East market was identified as a potential market for exit. This article examines the honey market of Ukraine, identifies the problems of the honey market and market’s prospects in the context of the spread of Сovid-19. The attractiveness of the international business environment of the Middle East is estimated in order to find potential markets for Ukrainian honey producers. An analysis of the Middle East countries for export of honey of Ukrainian producers based on a filter model. In the process of analyzing the Middle East market on the basis of a filter model, countries were selected by factors of macromarketing environment and introindustry environment. Moreover, each of the factors that helped determine potential market in the final of the research was assessed by author. The analysis of key filters revealed a high level of the Middle East integration into the system of world economic relations, the constant expansion of their cooperation with other countries, positive dynamics of economic growth indicators. Comparing different countries, a potential country for expanding the geography of sales of Ukrainian honey is suggested.